Combined size and texture-dependent deformation and strengthening mechanisms in Zr/Nb nano-multilayers. (1st February 2017) - Callisti, M.; Polcar, T.
Abstract: A combination of transmission electron microscopy analyses and nanomechanical measurements was performed in this study to reveal deformation and strengthening mechanisms occurring in sputtered Zr/Nb nanoscale metallic multilayers (NMMs) with a periodicity ( L ) in the range 6–167 nm. Electron diffraction analyses revealed a change in the crystallographic orientation of α-Zr when L  ≤ 27 nm, while Nb structure retained the same orientations regardless of L . For L  > 60 nm, the strengthening mechanism is well described by the Hall-Petch model, while for 27 <  L  < 60 nm the refined CLS model comes into picture. A decrease in strength is found for L  < 27 nm, which could not be simply explained by considering only misfit and Koehler stresses. For L  ≤ 27 nm, plastic strain measured across compressed NMMs revealed a change in the plastic behaviour of α-Zr, which experienced a hard-to-soft transition. At these length scales, the combination of two structural factors was found to affect the strength. These relate to the formation of weaker interfaces which extend the effective distance between strong barriers against dislocation transmission, thus producing a softening effect. The second effect relates to the crystallographic orientation change exhibited by α-Zr for L  < 27 nm with a consequent change of the dominant slip system. The actual strength at these smaller length scales was effectively quantified by taking these structural aspects into account in the interface barrier strength model. Graphical abstract: Image 1